Non-Wood Forest Products Collection and its Economic Valuation in Godhra Forest Division of Gujarat, India - Yadav, Rajkumar; Mewada, Ketan; Rajpurohit, Sweta; Kamboj, R. D. (Indian Forester, 2018)
The Non-wood Forest Products (NWFPs) or Non-timber Forest Products (NTFPs) have shown a great contribution to the tribal economy, in the international, national and regional markets and this have abundant economic significance for them. The present study was initiated through the primary survey of households to estimate the total collection and the value of NWFPs. After extrapolation of the primary data, it was found that the Godhra Forest Division showed tremendous diversity i.e., 45 different types of NWFPs which can be categorized into leaves, flowers and seed, gums, tanning materials, herbs, fruits and Bamboos and other miscellaneous items. The evaluation shows that the maximum economic value comes from flowers and seeds, ` 187.4 million/annum (55%) followed by leaves, ` 71.09 million/annum (21%), fruits, `40.1 million/annum (12%) Bamboo, ` 16.4 million/annum (5%), herbs and miscellaneous, ` 15.08 million/annum (4%) and gum and tanning materials ` 11.4 million/annum (3%). Thus, a total of `341.7 million/annum was contributed to the tribal economy of Godhra Forest Division while per capita and per household income are ` 340/ annum and `1970/annum, respectively.